PHANGS-JWST first results: spurring on star formation : JWST reveals localized star formation in a spiral arm spur of NGC 628 - Williams, Thomas G.; Sun, Jiayi; Barnes, Ashley T.; Schinnerer, Eva; Henshaw, Jonathan D.; Meidt, Sharon E.; Querejeta, Miguel; Watkins, Elizabeth J.; Bigiel, Frank; Blanc, Guillermo A.; Boquien, Médéric; Cao, Yixian; et al. (The astrophysical journal. Part 2, Letters, 2022)
We combine JWST observations with Atacama Large Millimeter/submillimeter Array CO and Very Large Telescope MUSE Hα data to examine off-spiral arm star formation in the face-on, grand-design spiral galaxy NGC 628. We focus on the northern spiral arm, around a galactocentric radius of 3-4 kpc, and study two spurs. These form an interesting contrast, as one is CO-rich and one CO-poor, and they have a maximum azimuthal offset in MIRI 21 μm and MUSE Hα of around 40° (CO-rich) and 55° (CO-poor) from the spiral arm. The star formation rate is higher in the regions of the spurs near spiral arms, but the star formation efficiency appears relatively constant. Given the spiral pattern speed and rotation curve of this galaxy and assuming material exiting the arms undergoes purely circular motion, these offsets would be reached in 100-150 Myr, significantly longer than the 21 μm and Hα star formation timescales (both < 10 Myr). The invariance of the star formation efficiency in the spurs versus the spiral arms indicates massive star formation is not only triggered in spiral arms, and cannot simply occur in the arms and then drift away from the wave pattern. These early JWST results show that in situ star formation likely occurs in the spurs, and that the observed young stars are not simply the “leftovers” of stellar birth in the spiral arms. The excellent physical resolution and sensitivity that JWST can attain in nearby galaxies will well resolve individual star-forming regions and help us to better understand the earliest phases of star formation.